Good times for everyone sexuality questions, feminist answers - Chandiramani, Radhika 1965- (New Delhi Women Unlimited, 2008)
Indian cases; in question-answer form.
pt. 1. Anatomy : what it looks like and how it worked -- pt. 2. LGBT : what am I and does it matter? -- pt. 3. Sex : good times for everyone -- pt. 4. Sexual health : how to keep it safer -- pt. 5. Emotional intelligence : making relationships work -- pt. 6. Resources : what to know more?
"Published in collaboration with Tarshi"--T.p. verso.
UCWS-2014-G-1627 donated by Ankit Gupta
Keywords: Sex counseling -- India